Generation of Offshore Environments in the Numerical Wave Tank to Model Metocean Conditions Interaction with Offshore Structure Near the Free Surface - Ahmed, M. (IOP Publishing Ltd, 2021)
Offshore structures play a vital role in the economy of offshore oil-producing countries, where mostly fixed jacket type structures are used to produce oil and gas installed in shallow water. In an offshore environment where structures are installed, there exist met ocean forces such as wind, waves, and currents. These met ocean conditions when interacting with offshore structures near the free surface, generate loads. The estimation of such loads is very much important for the proper design of these structures. The primary aim of this study is to investigate the interaction of waves with a jacket platform by generating offshore environments in the numerical wave tank (NWT). To achieve this goal, ANSYS Fluent is used for the flow analysis by using continuity and Navier Stokes equation. Results are verified and validated with the analytical work. Wave crests under operating condition generate a force of 1.3 MN which is the lowest in magnitude as compared to wave crest which produces 4.5 MN force under extreme conditions. Unlike operating wave crest, the operating wave trough generates a higher force of 1 MN than extreme conditions which account for 1.5 MN forces. Forces produced by the extreme offshore environment are 30 higher than those generated under operating conditions. It is concluded from the results that a positive force is exerted onto the structure during the water entry phase while a negative force is observed when the water leaves the structure. Â© Published under licence by IOP Publishing Ltd.